Gender and socially inclusive WASH in Nepal: moving beyond “technical fixes” - Khadka, Manohara; Joshi, Deepa; Uprety, Labisha; Shrestha, Gitta (Frontiers in Human Dynamics, 2023)
The enactment of a new Constitution in 2015 in Nepal marked a shift to a representative system of federal governance. Earlier in 2002, the country's Tenth Five Year Plan had committed to a core focus on gender equality and social inclusion (GESI) in national policies and governance. How do these two strategic shifts in policy align in the case of WASH projects in rural Nepal? Applying a feminist political lens, we review the implementation of WASH initiatives in two rural districts to show that deep-rooted intersectional complexities of caste, class, and gender disallow inclusive WASH outcomes. Our findings show that the policy framing for gender equitable and socially inclusive outcomes have not impacted the WASH sector, where interventions continue as essentially technical interventions. While there has been significant increase in the number of women representatives in local governance structures since 2017, systemic, structural biases by caste, ethnicity and gender entrenched across institutional structures and cultures persist and continue to shape gender-power dynamics. This is yet another example that shows that transformative change requires more than just affirmative policies. 1 We defined the marginalized groups in this paper as individuals or groups who are economically poor and socially marginalized due to their caste, ethnicity, class and other identities. They include the poor, Dalits, people living with disability and indigenous ethnic groups.